Ban Lee Heng Motor Sdn Bhd / Khairunnisa Suhaimi - Suhaimi, Khairunnisa (Faculty of Business and Management, 2023)
"An internship is not just a stepping stone; it's a launch pad that propels you towards your dreams and prepares you for the journey ahead." Industrial training is the gateway to practical knowledge and hands-on experience, where theory meets reality, shaping students into a skilled professional and empowering student to excel in the world of industry. This phrase is appropriate for characterizing an exciting and meaningful experience during my 6-month industrial training from 1 March 2023 to 15 August 2023 at Ban Lee Heng Motor Sdn Bhd in the Account Department. The internship program aimed to provide an in-depth understanding of accounting operations, financial processes, and the overall functioning of the organization. This report includes a summary of the firm as well as my internship experience. An introduction to the overall firm background, including the vision and mission, organisational structure, and products provided. I have also included an updated version of my resume that includes the details of my internship experience. I have included my training perspective in the following section, where I go into greater detail. Thus, I have written an observation regarding the company, which identified the company's SWOT analysis in terms of its strengths, weaknesses, opportunities, and threats. Additionally, there are recommendations and deeper explanations of the discussions. conclusion, the internship at Ban Lee Heng Motor Sdn Bhd's Account Department was a rewarding experience, providing valuable insights into accounting practices and the automotive industry. The intern's time at the company significantly contributed to their personal and professional development, and they express sincere gratitude to the organization and the team for their support and guidance throughout the internship.